2023
DOI: 10.1007/s10457-023-00845-z
|View full text |Cite
|
Sign up to set email alerts
|

Agronomic performance of soybean and sorghum in a short rotation poplar coppice alley-cropping system under Mediterranean conditions

Abstract: The transition from conventional arable towards silvoarable systems can increase the delivery of ecosystem services. Nevertheless, the assessment of crop yield under agroforestry condition is crucial to evaluate of the reliability of these systems and to increase the knowledge base needed to support their design. Although the feasibility of poplar short rotation coppice (SRC) silvoarable alley-cropping systems has been widely investigated, few studies have addressed the agronomic response of crops intercropped… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…After the forage legume cultivation the choice of the right herbaceous grain crop is crucial in AC systems to maximize facilitation (e.g., to exploit residual N in the soil) and minimize competition with trees. Warm-season crops, for example, can benefit from reduced potential evapotranspiration by leveraging the windbreaking function of tree rows, especially in rainfed systems (Mantino et al 2023). Previous studies have shown the viability of intercropping sorghum (Sorghum bicolor L.) with poplar in AC under rainfed Mediterranean conditions (Pecchioni et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…After the forage legume cultivation the choice of the right herbaceous grain crop is crucial in AC systems to maximize facilitation (e.g., to exploit residual N in the soil) and minimize competition with trees. Warm-season crops, for example, can benefit from reduced potential evapotranspiration by leveraging the windbreaking function of tree rows, especially in rainfed systems (Mantino et al 2023). Previous studies have shown the viability of intercropping sorghum (Sorghum bicolor L.) with poplar in AC under rainfed Mediterranean conditions (Pecchioni et al 2020).…”
Section: Introductionmentioning
confidence: 99%